PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PEMBELAJARAN KONTEKSTUAL DENGAN MEDIA AUDIO VISUAL - Hati Wahyuni (MEDIA DIDAKTIKA, 2021)
The purpose of this class action research is to improve teacher skills, student activities, and student learning outcomes through contextual learning models with audio visual media. This type of research is classroom action research conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The study was conducted at Gondanglor II Elementary School, Sugio Subdistrict, Lamongan Regency. The technique of collecting data uses tests, non tests, observations, and documentation. Data analysis techniques by means of descriptive, quantitative and qualitative analysis. The results showed that: the skills of the first cycle teachers scored 23 (good category), cycle II scored 30 (very good category). The activity of students in the first cycle obtained an average score of 2.49 (good category), in the second cycle the average score was 3.00 (good category). The percentage of classical completeness of learning outcomes in the first cycle was 67.3%, cycle II increased to 93.3%.